Risk Assessment and Prevention of Falls - Sri Pudji, Sri Pudji; Kusnadi, Kusnadi (The Indonesian Journal of General Medicine, 2024)
Background: The literature surrounding the risk assessment and prevention of falls among the elderly has seen significant developments over the past decade, highlighting a multifaceted approach to understanding and mitigating this prevalent issue. Literature Review: Following this foundational work, (Gryn, 2017) emphasizes the importance of an interdisciplinary team approach, demonstrating that collaborative interventions can effectively reduce falls by 20-30%. This underscores the necessity for comprehensive strategies that incorporate diverse healthcare professionals. (C Slade et al., 2017) further contribute to this discourse by focusing on reversible risk factors in hospitalized adults, advocating for systematic reviews to delineate effective strategies for fall prevention within institutional settings. Complementing this, (Francis-Coad et al., 2018) explore the perspectives of older adults in residential care, revealing significant gaps in knowledge and awareness that hinder effective engagement with prevention strategies. Conclusion: In conclusion, the body of literature reviewed illustrates the multifaceted nature of fall risk assessment and prevention among the elderly. It underscores the importance of interdisciplinary approaches, the integration of technology, and the development of standardized guidelines to effectively address the complexities of fall prevention. The collective findings call for a concerted effort to implement individualized interventions, enhance knowledge and awareness among older adults, and promote collaborative strategies across healthcare settings.